Students’ Attitude toward the Implementation of Teaching Listening Using Dictoglos Technique - Susanti, Yunik (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2014)
ABSTRACT Listening is the basis for the development of all other skills and the main channel through which the learner makes initial contact with the target language and its culture. Dictogloss technique is a classroom dictation activity in which learners listen to a passage, note down key words and then work together to create a reconstructed version of the text. This activity combines individual and group activities. The students’ attitude toward its implementation in listening teaching learning process in investigated in this study. It is a case study in the second year students of English Department Faculty of Teacher Training Nusantara PGRI Kediri University. The subject of the study was 2C class that consists of 38 students. The structured interview and closed ended questionnaire were used to know the students’ attitude towards dictogloss. It was founded that the students have positive attitudes towards this technique especially in the affective aspect.It is suggested that the English teacher should use dictogloss technique in teaching listening comprehension since it the students found it interesting and challenging for them to be  more active in teaching and learning process. Key word: Teaching Listening, Dictogloss, Students’ Attitude